Implementasi Cyber Public Relations dalam Mempertahankan Citra: Studi Deskriptif Data Kualitatif di BAZNAS Provinsi Jawa Barat - Tasya Irvanti Novitasari; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2023)
Abstract. Public distrust of philanthropic institutions and the like after the misappropriation of funds by well-known philanthropic institutions in the country became warm in the middle of 2022. PR plays an important role in maintaining the image of the institution. Not on the West Java BAZNAS, which the West Java Provincial Government relies on. Dissemination of information by PR is very important because of the public's understanding of a large institution in the formation of institutions. The use of the internet makes the dissemination of information not limited by space and time. Therefore, Cyber Public Relations can be one way to maintain the image of the institution. This study aims to: (1) Know the content of the Interactive News Room; (2) Describe the preparation of Social Media News Releases; (3) Analyzing the use of Social Networks; and (4) Knowing the making of Audio Visual Communication as a form of cyber PR implementation by BAZNAS Jabar in maintaining the image. This study uses quantitative methods, descriptive approach with qualitative data collected through semi-structured interview, observation, and documentation. The results of this study are: (1) Website as an Interactive News Room which contains information on institutional information, publications, and ZIS services and programs; (2) Social Media News Release is prepared based on information from the DPP division and then visualized by design and/or video; (3) Facebook's social network is used for information media and closeness with the public; and (4) Audio Visual Communications are made in the form of ZIS programs and services video and edutainment videos that adapt popular trends. Abstrak. Ketidakpercayaan masyarakat terhadap lembaga filantropi dan sejenisnya pasca penyelewengan dana oleh lembaga filantropi terkenal di tanah air menjadi isu hangat di pertengahan tahun 2022. PR berperan penting mempertahankan citra lembaganya, tidak terkecuali pada BAZNAS Jabar yang diandalkan Pemprov Jabar. Penyebaran informasi oleh PR merupakan hal yang sangat penting karena pemahaman publik mengenai suatu lembaga berperan besar dalam pembentukan citra lembaga. Pemanfaatan internet membuat penyebaran informasi tidak terbatas oleh ruang dan waktu. Maka dari itu, Cyber Public Relations dapat menjadi salah satu cara dalam mempertahankan citra lembaga. Penelitian ini bertujuan untuk: (1) Mengetahui konten Interactive News Room; (2) Mendeskripsikan penyusunan Social Media News Release; (3) Menganalisis pemanfaatan Social Networking; dan(4) Mengetahui pembuatan Audio Visual Communication sebagai bentuk implementasi cyber PR oleh BAZNAS Jabar dalam mempertahankan citra. Penelitian ini menggunakan metode kuantitatif, pendekatan deskriptif dengan data kualitatif yang dikumpulkan melalui wawancara semi-terstruktur, observasi, dan dokumentasi. Hasil penelitian ini adalah: (1) Website sebagai Interactive News Room berisi konten informasi kelembagaan, publikasi, serta layanan dan program ZIS; (2) Social Media News Release disusun berdasarkan informasi dari divisi DPP kemudian divisualisasikan dengan desain dan/atau video; (3) Jejaring sosial Facebook dimanfaatkan untuk media informasi dan menjalin kedekatan dengan publik; dan (4) Audio Visual Communication dibuat berbentuk video program dan layanan ZIS dan video edutainment yang mengadaptasi tren populer.